Procedures in infants and children - Michel C Walsh-Sukys (W. B. Saunders, 1997)
The book focuses nearly exclusively on the cognitive aspects of practice. It is prepared to instruct students, residents, and practitioners in the art and science of pediatric procedures in a more systematic way